The Fundamentals of Case-Based Reasoning: Application to a Building Defect Problem - binti Abdullah, Salha (Malaysian Journal of Computer Science, 1997)
Traditional expert systems model human problem solving as a deductive process. They construct a solution by applying general rules to the description of a problem. Recently, however, it has become apparent that human experts rely heavily on memory of past cases when solving problems. This is the focus of systems using case-based reasoning (CBR) approach which is rapidly emerging as a powerfulexpert system approach that can overcome some weaknesses of traditional systems. The aim of the article is to demonstrate to the construction industry, how CBR can be applied in its sector. It presents an overview of CBR, depict characteristics that make a problem domain suitable for CBR and describe briefly the implementation of a CBR system and its findings.